Digital Transformation in the USA Leveraging AI and Business Analytics for IT Project Success in the Post-Pandemic Era - Hossin , Md Ekrim; Rahman, Md Mohibur; Hossain, Sazzat; Siddiqa, Kazi Bushra; Rozario, Evha; Khair, Fahmida Binte; Alam, Gazi Touhidul; Orthi, Shuchona Malek; Mahmud, Foysal (Journal of Posthumanism, 2025)
The researcher investigates the contributions of AI and business analytics to IT project triumphs through their enhancement of project administration procedures along with resource distribution management and predictive risk avoidance analytics. The aftermath of the pandemic forced businesses in the USA to speed up their digital transformations by implementing artificial intelligence and business analytics to achieve IT project fulfillment. Technologies that integrate enable better decisions as well as exposure and operational effectiveness that result in systems with greater resilience and agility. The research design combines qualitative data collection methods with quantitative data collection methods through a mixed-methods approach. IT professionals with project managers based in the USA participate in research surveys to measure AI and business analytic effects on project accomplishment results. The researcher study leading tech companies through case studies to identify vital success elements and effective practices. Project performance correlations alongside digital transformation initiative patterns be identified through machine learning models and statistical analysis techniques. This research delivers important information about AI and business analytics effectiveness in supporting IT project success after the pandemic ends. The integration of new technologies enables organizations to create more effective project management practices and retain lower operational risks while advancing their innovation capabilities. AI capabilities and data analytics prove essential to support sustainable digital transformation that competes in the constantly evolving IT sector of the United States.